FELCRA Berhad Sabah : a study on the fresh fruit bunches (FFB) buying price among palm oil mill / Irman Abok - Abok, Irman (2009)
This paper reports are focusing to "FELCRA Berhad Sabah : A study on the Fresh Fruit Bunches (FFB) buying price among palm oil mill". In order to achieve the objectives, 117 questionnaires distributed to palm oil mill that operating in state of Sabah. There are five main issue were discussed in this topic contained by 1) place of palm oil mill, 2) quality of Fresh Fruit Bunches (FFB), 3) cost of transportation, 4) cost of processing and 5) Fix cost fee. The conclusion on this paper is that, FELCRA should do some effort to hold the buying price even it determines by mill. Tender one of the solution to ensure the range of price that involves in marketing transaction will hold by FELCRA Berhad Sabah especially on buying price of Fresh Fruit Bunches (FFB).